The Design and Management of National Morbidity Surveys - Fleming, D. M. (Methods of Information in Medicine, 1991)
This paper describes the three major morbidity surveys in general practice which have been conducted in England and Wales. In it, the evolution of the recording method is traced from the patient summary card of the first survey to the diagnostic index of the second and third surveys and finally, to the fully computerised recording programme to be used in the fourth survey due to start in September, 1991. Issues relating to the capture of social data, the use of diagnostic terms and the value of obtaining data over a 12 month period are discussed.
Keywords: Morbidity Survey; Diagnostic Index; Age-sex Register; Computerised Practices; Social Data